1952
DOI: 10.1039/jr9520002773
|View full text |Cite
|
Sign up to set email alerts
|

524. Titanium chloride alkoxides

Abstract: described. These compounds distilled under reduced pressure without change in composition and the possibility that titanium exhibits here a covalency of 5 is considered. The new alkoxides TiCl,*OR where R = Me, Et, Pri, and Bun were readily obtained from the rapid radical-interchange reaction between the tetrachloride and the appropriate tetra-alkoxide. Certain of the titanium chloride alkoxides disproportionate when heated under reduced pressure.TITANIUM CHLORIDE ETHOXIDES have been known since 1875 when Dema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

1959
1959
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(26 citation statements)
references
References 0 publications
2
24
0
Order By: Relevance
“…Benzyl alcohol is coordinated to Nb centers in large amounts due to ligand exchange reactions. [216] The Scheme 3. Proposed side reaction involving a CÀC bond formation of two benzylic species to form 1,2-diphenylethanol occurring to a large extent upon solvothermal reaction of NbA C H T U N G T R E N N U N G (OEt) 5 in benzyl alcohol.…”
Section: Nonaqueous Sol-gel Chemistry For Metal Oxide Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…Benzyl alcohol is coordinated to Nb centers in large amounts due to ligand exchange reactions. [216] The Scheme 3. Proposed side reaction involving a CÀC bond formation of two benzylic species to form 1,2-diphenylethanol occurring to a large extent upon solvothermal reaction of NbA C H T U N G T R E N N U N G (OEt) 5 in benzyl alcohol.…”
Section: Nonaqueous Sol-gel Chemistry For Metal Oxide Synthesismentioning
confidence: 99%
“…It is known that such ligand-exchange processes take place already at room temperature. [216,217] Next the alkoxy species undergo condensation to form M À O À M bonds and organic ether [Eq. (17)].…”
Section: Nonaqueous Sol-gel Chemistry For Metal Oxide Synthesismentioning
confidence: 99%
“…The first pressure increase is mainly due to the VLE and additional 1-propanol that is released by a ligand exchange. Several authors have shown that the ligand exchange reaction of transition metal alkoxides in organic solvents commences already at ambient temperatures [29][30][31] and can be assumed to be completed before the reaction mixture reaches the final temperature. 32 Moreover, one can observe a slight but immediate pressure decrease after the heating period ( Fig.…”
Section: Figmentioning
confidence: 99%
“…Chlorotitanium esters are best produced, however, by the reaction of stoichiometric quantities of titanium tetrachloride with titanium esters (7,41).…”
Section: Acidolysismentioning
confidence: 99%